Community education for solid waste management: Knowledge gains in rural area, Pangkep, Indonesia - Kurniawan, Irfan; Samsiana, Samsiana; Mujtahidah, Mujtahidah; Mappanyuki, Andi Atssam; Afdhal, Muhammad Ridha (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Although community education is increasingly used to improve solid waste practices, evidence from rural Indonesian villages remains limited, and few programs combine Participatory Rural Appraisal (PRA) with rapid pre–post evaluation; this initiative addresses that gap by testing a community-based educational program in Balocci Baru Village, Pangkep Regency, Indonesia. The program, entitled “Smart Waste Management, Smart Environmental Stewardship,” aimed to strengthen community knowledge and understanding of proper, responsible, and sustainable waste management to reduce environmental contamination and downstream public health risks. Using a participatory PRA approach, educational sessions were delivered to 22 participants (community members, health cadres, and local leaders) and evaluated through pre-test and post-test measurements. Visual reinforcement tools (posters and informational boards) were integrated to support comprehension and recall. Post-intervention results indicated a clear improvement in knowledge distribution, with no participants remaining in the low-knowledge category. Statistical testing using the Wilcoxon signed-rank test confirmed a significant increase in knowledge scores (p < 0.05). These findings suggest that participatory, visually supported education can be an effective entry point for community-driven waste management in rural settings, with potential adaptation for peri-urban and urban neighborhoods where waste generation and exposure pathways differ but behavior change remains central to environmental health promotion.